1988
DOI: 10.1099/00222615-25-1-27
|View full text |Cite
|
Sign up to set email alerts
|

A survey of IgA protease production among clinical isolates of Proteeae

Abstract: Summary.A collection of 100 strains of Proteeae, in which all species within the tribe were represented, was examined for IgA protease production. The strains were isolated from various clinical specimens from sick and healthy persons in several countries. IgA protease-producing strains were not found amongst species of Providencia and Morganella but were common in Proteus spp. All the strains of P. mirabilis and P. penneri and many of the strains of P. vulgaris examined produced an EDTA-sensitive protease tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 26 publications
3
13
0
Order By: Relevance
“…Identical results were obtained when the native P. mirabilis enzyme was used. These results agree with the results obtained by Loomes et al (47), who have reported that numerous Proteus strains secrete an EDTA-sensitive metalloprotease (58,59).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Identical results were obtained when the native P. mirabilis enzyme was used. These results agree with the results obtained by Loomes et al (47), who have reported that numerous Proteus strains secrete an EDTA-sensitive metalloprotease (58,59).…”
Section: Resultssupporting
confidence: 93%
“…The enzyme also cleaves secretory component, casein, gelatin, and BSA (47). Many of the data obtained in this study from both the native P. mirabilis metalloprotease and the E. coli recombinant enzyme agree with the findings of Loomes et al (45)(46)(47)(57)(58)(59). The relative molecular weight, divalent cation requirement, and substrate specificity are similar to those of previous reports, suggesting that the enzyme we have analyzed and whose gene we have cloned shares features with the enzyme studied by Loomes et al (47).…”
Section: Discussionsupporting
confidence: 90%
“…mirabilis has multiple mechanisms to evade host defenses, including the extracellular metalloprotease ZapA (27,28), also referred to as an IgA protease (24,25). ZapA is expressed in many strains of P. mirabilis (24).…”
mentioning
confidence: 99%
“…In 1992, Pouedras et al demonstrated that a human isolates of P. multocida capsule type D from pulmonary infection and another from genital infection, produced extracellular proteases that cleaved human IgA and IgG. As it is known that bacteria adapted to mucosal surfaces often express such enzymatic activity (Molla et al, 1988;Senior et al, 1988) it would not be surprising if more P. multocida isolates from different sources were shown in the future to produce such enzymes. One difficulty concerning the detection of these enzymes is that protease production may disappear following only a few subcultures (Pouedras et al, 1992).…”
Section: Other Enzymesmentioning
confidence: 99%